2014
DOI: 10.4066/amj.2014.2235
|View full text |Cite
|
Sign up to set email alerts
|

An educational intervention’s effect on healthcare professionals’ attitudes towards pharmacovigilance

Abstract: The intervention was effective in improving HCPs' knowledge of and attitude towards pharmacovigilance and consumer pharmacovigilance. More studies on this topic among HCPs at other institutions and in the community are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
5
10
0
Order By: Relevance
“…These include the use of didactic lectures, presentations, posters relating to pharmacovigilance and ADR reporting, different modes of reminders, use of safety bulletins and safety newsletters among others. 1317 Rates of success of the strategies varied depending on the type of HCP. It has also been shown that a multidimensional approach to changing provider behaviour is key to a successful intervention.…”
Section: Introductionmentioning
confidence: 99%
“…These include the use of didactic lectures, presentations, posters relating to pharmacovigilance and ADR reporting, different modes of reminders, use of safety bulletins and safety newsletters among others. 1317 Rates of success of the strategies varied depending on the type of HCP. It has also been shown that a multidimensional approach to changing provider behaviour is key to a successful intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The national pharmacovigilance centre run by the DDA, coordinates with seven regional pharmacovigilance centres to collect ADR reports which are forwarded to the Uppsala Monitoring Centre in Sweden, a centre for international service and scientific research towards patient safety [21]. Till date, the ADR reporting system does not involve community pharmacists and consumers and depends on voluntary reporting from other healthcare professionals, predominantly doctors, hospital pharmacists and nurses [22]. …”
Section: Introductionmentioning
confidence: 99%
“…10 Similar study was done in Nepal which showed there is no involvement of consumers in ADR reporting still and it has been dependent on reporting by the healthcare professionals. 11 Similar study was done in China showed that consumers with a higher level of education were having a greater level of knowledge and awareness about ADRs. 12 A study done in Sri Lanka during mass treatment regimen for filariasis regarding the general people's awareness about ADR revealed that there was no significant association between the area of residence of the participants and their likelihood to report any experience of ADRs.…”
Section: Discussionmentioning
confidence: 65%